2007
DOI: 10.1093/jhered/esm001
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of Alectoris chukar Genes into a Spanish Wild Alectoris rufa Population

Abstract: In order to detect introgression of other Alectoris genus species into wild populations of Spanish Alectoris rufa, we studied a sample of 93 red-legged partridges (supposed to be A. rufa) captured in the island of Majorca. A set of 31 chukar partridges (Alectoris chukar) from Cyprus and 33 red-legged partridges (A. rufa) from one Spanish farm were also studied to provide suitable populations for comparison. Factorial correspondence analysis on microsatellite genotypes supported a clear distinction of birds fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
1
22
1
Order By: Relevance
“…This proved to be a wild partridge from Northern Sardinia, showing a limited (10%) trace of A. rufa DNA in its ancestry. This result strikingly differs from those recently reported for other European partridge populations, where human-caused widescale hybridization seemed to be the rule (Negro et al 2001;Baratti et al 2005;Barbanera et al 2005;Barilani et al 2007a, b;Tejedor et al 2007). In addition, the analysis of individuals sampled in four breeding stations showed levels of genetic variation similar to that in the wild population, while no sign of hybridization was found.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…This proved to be a wild partridge from Northern Sardinia, showing a limited (10%) trace of A. rufa DNA in its ancestry. This result strikingly differs from those recently reported for other European partridge populations, where human-caused widescale hybridization seemed to be the rule (Negro et al 2001;Baratti et al 2005;Barbanera et al 2005;Barilani et al 2007a, b;Tejedor et al 2007). In addition, the analysis of individuals sampled in four breeding stations showed levels of genetic variation similar to that in the wild population, while no sign of hybridization was found.…”
Section: Discussioncontrasting
confidence: 92%
“…Multilocus genotyping techniques have already shown to be useful tools for assessing levels of genetic variation and population structure (Randi et al 2003;Tejedor et al 2005;Chen et al 2006;Arruga et al 2007), as well as resolving interspecific hybridization processes in Alectoris taxa (Baratti et al 2005;Barilani et al 2007a, b;Tejedor et al 2007). The microsatellite markers used in these studies had been isolated in the chicken (Gallus gallus) and revealed to be polymorphic in species of the genus Alectoris (Baratti et al 2005), as well as in other Galliformes (Baratti et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Females being the heterogametic sex in birds, Haldane's rule would also predict that mitochondrial haplotypes show patterns of reduced introgression compared with nuclear alleles (Carling and Brumfield, 2008). However, several cases of interspecific gene flow documented in birds depicted the reverse pattern; no nuclear introgression is detected while the maternally transmitted mtDNA exhibits high levels of introgression (Tejedor et al, 2007;Bellemain et al, 2008;Irwin et al, 2009). This is the same pattern we observed between the North American L. marinus and the sympatric L. smithsonianus.…”
Section: Resultssupporting
confidence: 72%
“…Recent molecular studies on nuclear and/or maternal markers show a significant incidence of chukar genes in most of the A. rufa populations investigated so far. Chukar introgression (A. rufa x A. chukar hybridization) was detected in 45 % of wild populations in the Iberian Peninsula (Blanco-Aguiar et al 2008), and in 17.2 % in Majorca Island (Tejedor et al 2007). Introgression of A. chukar nuclear or mitochondrial DNA have been also described in 30 % of A. rufa populations investigated in southern France (Vallance et al 2006), in 28 % of natural red-legged x rock partridge hybrids in the French Alpes-Maritimes (Barilani et al 2007a), and in Corsican A. rufa populations with frequencies up to 67 % (Barbanera et al 2010).…”
Section: Discussionmentioning
confidence: 99%